Long noncoding RNAs involve in resistance to Verticillium dahliae, a fungal disease in cotton. Issue 6 (21st December 2017) - Zhang, Lin; Wang, Maojun; Li, Nannan; Wang, Honglei; Qiu, Ping; Pei, Liuling; Xu, Zheng; Wang, Tianyi; Gao, Erlin; Liu, Junxia; Liu, Shiming; Hu, Qin; et al.
Summary: Long noncoding RNAs (lncRNAs) have several known functions in plant development, but their possible roles in responding to plant disease remain largely unresolved. In this study, we described a comprehensive disease‐responding lncRNA profiles in defence against a cotton fungal disease Verticillium dahliae . We further revealed the conserved and specific characters of disease‐responding process between two cotton species. Conservatively for two cotton species, we found the expression dominance of induced lncRNAs in the Dt subgenome, indicating a biased induction pattern in the co‐existing subgenomes of allotetraploid cotton. Comparative analysis of lncRNA expression and their proposed functions in resistant Gossypium barbadense cv. '7124' versus susceptible Gossypium hirsutum cv. 'YZ1' revealed their distinct disease response mechanisms. Species‐specific (LS) lncRNAs containing more SNPs displayed a fiercer inducing level postinfection than the species‐conserved (core) lncRNAs. Gene Ontology enrichment of LS lncRNAs and core lncRNAs indicates distinct roles in the process of biotic stimulus. Further functional analysis showed that two core lncRNAs, GhlncNAT‐ANX2‐ and GhlncNAT‐RLP7‐ silenced seedlings, displayed an enhanced resistance towards V. dahliae and Botrytis cinerea, possibly associated with the increased expression of LOX1 and LOX2 . This study represents the first characterization of lncRNAs involved in resistance to fungal disease and provides new clues to elucidate cotton disease response mechanism.